Non-Moro IP Inclusion in Education Governance: Historical Notes on Institutional Policies and IP Population in MSU-IIT, Iligan City - Almario-Magdadaro, Marjorie; Otano, Jed; Collantes, Lyra Joy (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This article presents a historical overview of institutional initiatives concerning the inclusion of Non-Moro Indigenous Peoples as indicators of good governance in education. This underscores the importance of not only integrated but an inclusive education for every student from both the mainstream and the margins. Gleaned from the experience of MSU-Iligan Institute of Technology (MSU-IIT), this study elaborates the following: (1) what are the policies and programs contributing to the inclusion of Non-Moro IPs in MSU-IIT, and (2) how MSU-IIT administered the Non-Moro IP population and what are the challenges encountered. This research utilized qualitative methods with data coming from MSU-IIT offices and online databases, corroborated with purposive-snowball interviews. Discussions show that the IP students have faced a number of obstacles that have interfered with their college experience, whether they relate to admissions or retention including dropping out of classes, financial constraints and struggle in major coursework leading to the necessary improvement on their overall scholastic performance. MSU-IIT has also responded to the challenge of exclusion through, but not limited to, the General Education Program, the Five-Year Development Plan covering Education and Student Support Pillars, the Equity, Diversity, and Inclusivity (EDI) Policy, and other academic and non- academic pathway initiatives.